Strategi Islamic Marketing dalam Meningkatkan Penjualan Usaha Pancake Durian Tri Putri di Desa Payaman Kecamatan Solokuro Kabupaten Lamongan - Faizatul Umroh; Dymas Yulia Putri Kusumaningtyas (Al-Muzdahir : Jurnal Ekonomi Syariah, 2021)
Tri Putri Durian Pancakes in Payaman Village are Home Industry. Tri Putri Durian Pancake products are currently in great demand by the public, especially among young people, this is shown by the Tri Putri Durian Pancake Marketing which has now expanded in several cities, including Lamongan City, to other cities such as Surabaya, Gresik, and Tuban. The location of Tri Putri Durian Pencake is in Payaman Village, Solokuro District, Lamongan Regency.This study aims to answer, describe, and analyze the formulation of the problem, namely how marketing is used for Tri Putri Durian Pancakes in Payaman Village, Solokuro District, Lamongan Regency and How is the Islamic marketing strategy in increasing sales of Tri Putri Durian Pancakes in Payaman Village, Solokuro District, Lamongan Regency. . The method used in this research is descriptive qualitative research method. The data collection technique of the researcher used the method of observation, interviews and documentation.The results of this study concluded that First Tri Putri Durian Pancakes in Payaman Village had implemented a 7P marketing mix strategy, namely product, price, promotion, place, people, process, and physical evidence that were able to increase sales at Tri Putri Durian Pancakes in Payaman Village. The marketing mix strategy that has been implemented by Pancake Durian Tri Putri in an effort to increase sales has also been carried out properly and correctly and in accordance with existing theory. The two Islamic Marketing Strategies in Tri Putri Durian Pencake Payaman Village viewed from the perspective of Islamic Economics it can be seen that the strategy used by Tri Putri Durian Pencake Payaman Village is in accordance with Islamic marketing theory such as: Theitis (robbaniyah) religious marketing, Ethical (akhlaqiyyah) Prioritizing moral issues (moral, ethical), realistic (al waqiiyah) being a flexible marketer, and humanistic (al insaniyyah) is a human trait. By implementing these Islamic Marketing strategies, it is hoped that the sales of Durian Pancake products carried out by Tri Putri Durian Pencakes in Payaman Village will experience success both in this world and in the hereafter